Drivers of Bushmeat Hunting and Perceptions of Zoonoses in Nigerian Hunting Communities - Friant, Sagan; Paige, Sarah B.; Goldberg, Tony L. (PLOS Neglected Tropical Diseases, 2015)
Author Summary Bushmeat hunting threatens biodiversity and increases the risk of disease transmission from animals to people. Using interview methods, we described patterns of hunting, potential pathways for zoonotic disease transmission, and drivers of hunting behavior in hunting communities in Southeast Nigeria. Participants contacted a diversity of wildlife through multiple pathways, but were not generally aware of wildlife zoonoses and typically took no or inadequate protective measures. Bushmeat was highly preferred over domestic alternatives, but there was a negative view of hunting as a livelihood, even among hunters themselves. Family size, age, education and family and cultural tradition influenced whether individuals hunted. Wildlife were hunted for many reasons other than consumption, indicating the importance of alternative pathways for zoonotic disease transmission. In this setting, sociocultural factors appear to be more important drivers of hunting behavior (and zoonotic disease risk) than previously appreciated. Our results will help inform policies aimed at modifying the impact of hunting on African forest wildlife and preventing zoonotic disease transmission.